ACTUAL ISSUES OF THE CURRENT STATE OF WAGES IN UKRAINE (INNOVATIVE ECONOMY, 2019)
Honchar L.V., Harna S.O., Shnurko A.M. ACTUAL ISSUES OF THE CURRENT STATE OF WAGES IN UKRAINEPurpose. The aim of the article is to research the topical problems of the current state of wages in Ukraine, identification of the primary causes of low wages and determination of ways of their solution.Methodology of research. Methodological basis for the study was the scientific methods of cognition, based on a systematic approach to solving the tasks. A number of general and special scientific methods of research is used to achieve this goal and to obtain the results of the research: dialectical; monographic (when working on scientific publications); systematic analysis (when examining the state of wages in Ukraine); method of analogies and comparisons (in the study of minimum wages of EU countries); comprehensive analysis (in formulating conclusions and proposals for solving problems) and others.Findings. The problematic issues of the current state of wages in Ukraine are investigated. The optimal ways of solving the problem of wages in our state, among which are the following: study of the leading Western experience; active participation of the state in the regulation of remuneration; improving the tariff system and normalization of labour; increase part of wages in the cost products (through wage deduction); reducing the amount of arrears of wages and salaries, etc.Originality. Complex approach to solving problematic wages of workers in our state, which allowed highlighting the possibility of qualitative improvement of its condition and creating a basis for increasing the interest of employees to high-performance work in the near future, is used in the article.Practical value. These suggestions will provide an opportunity to overcome the problems of the current state of wages in Ukraine.Key words: cost of living; wages; arrears; salary; labour productivity; labour force; functions of wages.
Keywords: Key words; cost of living; wages; arrears; salary; labour productivity; labour force; functions of wages.